The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4314/ahs.v17i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of long-acting reversible contraceptive devices in Western region of the Gambia

Abstract: Background: The contraceptive method has become an essential factor in the life of most women of reproductive age group; although it varies in different stages of their life course. The use of long acting reversible methods (LARC) is proposed as a strategy to reverse undesirable maternal health consequences in developing countries. Objective: To determine the uptake of long-acting reversible contraceptive in The Gambia. Methods: A community based cross-sectional study of women attending family planning clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
4
9
1
Order By: Relevance
“…The uptake of LARC in this study was 72.6%. This was similar to the rate reported by Dassah et al in Kumasi Ghana (70%) and ACOG among American women of 75% [4,9] but lower than the rate obtained in Enugu (90.2%) [10] and Gambia (88.7%) [11] . It was however higher than the reported rates of 26% in Malawi [12] , 38.7% in Kaduna [13] , 10.6% in Nnewi [14] , and that of the 2013 Nigerian health and demographic survey [1] .…”
Section: Discussionsupporting
confidence: 90%
“…The uptake of LARC in this study was 72.6%. This was similar to the rate reported by Dassah et al in Kumasi Ghana (70%) and ACOG among American women of 75% [4,9] but lower than the rate obtained in Enugu (90.2%) [10] and Gambia (88.7%) [11] . It was however higher than the reported rates of 26% in Malawi [12] , 38.7% in Kaduna [13] , 10.6% in Nnewi [14] , and that of the 2013 Nigerian health and demographic survey [1] .…”
Section: Discussionsupporting
confidence: 90%
“…Almost half of women who selected the IUD had a secondary education or higher, while 71% of implant users had no or only primary education. Most studies have found that higher education is associated with LARC uptake [37, 38], but these studies have not compared demographic differences in IUD versus implant uptake. It is possible that less educated women are still exposed to and aware of the hormonal implant simply because it is a more well-known method, but that only women with higher education are receiving information about the IUD.…”
Section: Discussionmentioning
confidence: 99%
“…Huda et al also mentioned OCP as the first choice, followed by contraceptive injections after reviewing ten FP articles of Bangladesh related to contraceptive practices among married women of reproductive age [ 26 ]. In some places in Africa [ 27 ], after having a child long-acting reversible contraceptive (LARC) was found at the highest rate in contraceptive use. Use of condom as contraceptive was less than 5% in rural community that showed minimum male participation in fertility control and it was also matched with the findings of BDHS [ 8 ].…”
Section: Discussionmentioning
confidence: 99%